2019
DOI: 10.1002/adfm.201906653
|View full text |Cite
|
Sign up to set email alerts
|

Air Effect on the Ideality of p‐Type Organic Field‐Effect Transistors: A Double‐Edged Sword

Abstract: Organic field-effect transistors (OFETs) often deviate from ideal behaviors in air, which masks their intrinsic properties and thus significantly impedes their practical applications. A key issue of how the presence of air affects the ideality of OFETs has not yet been fully understood. It is revealed that air atmosphere may exert a double-edged sword effect on the active semiconductor layer when determining the ideality of OFETs fabricated from p-type crystalline organic semiconductors. Upon exposing the as-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
(121 reference statements)
1
22
0
Order By: Relevance
“…Figures 1c,d schematically illustrate the BGTC OFET and the energy levels of each layer used in this research, respectively. The LUMO level and highest occupied molecular orbit (HOMO) level of dif‐TES ADT were reported at −3.04 and −5.14 eV, [ 31 ] respectively, as illustrated in Figure 1d. And the work function of thermal evaporated Au electrodes used in this research was measured to be 4.83 eV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figures 1c,d schematically illustrate the BGTC OFET and the energy levels of each layer used in this research, respectively. The LUMO level and highest occupied molecular orbit (HOMO) level of dif‐TES ADT were reported at −3.04 and −5.14 eV, [ 31 ] respectively, as illustrated in Figure 1d. And the work function of thermal evaporated Au electrodes used in this research was measured to be 4.83 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[41,42] When a large positive gate bias is applied, energy levels of dif-TES ADT will shift down by the gate field, hence electrons could be injected from the drain electrode to the LUMO level through thermionic field emission (as illustrated in Figure 1e). [31] It has been evidenced that these injected electrons could be readily captured by the water and oxygen absorbed in the active layer or at the dielectric surface, inducing undesired trapping effects. [21,34] Suffering from the electron injection effect, the as-fabricated device usually shows a typical double-slope behavior, exhibiting a peak transconductance (g m ) at low gate voltage (V G ) region, as shown in Figure 1f.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the nonidealized behavior not only limits the current driving capability but also reduces the switching speed of device, which severely hampers their practical applications. [9,10] Recently, great efforts have been focused on exploring the originations of the non-idealized behavior of PFETs, and concluded that trapping centers at polymer semiconductor (PSC)/ dielectric interfaces, [11][12][13][14] Coulombic interactions between charge carriers, [15][16][17] contact resistance effects, [18][19][20] and air effects [21,22] are the primary sources. Among them, the existence of trapping centers at PSC/dielectric interfaces is well accepted to explain the non-idealized behaviors of PFETs in air atmosphere.…”
Section: Introductionmentioning
confidence: 99%